THE ‘SOCIETAS LEONINA’ IN THE WORK OF COMMENTATORS - Palmirski, Tomasz (Zeszyty Prawnicze, 2019)
In Roman law a societas was a contract concluded between two or more persons with the purpose of sharing profts and losses. In the first place they were divided according to the provisions of the agreement, but a partnership in which one of the partners was only liable for loss and excluded from sharing in the profit was prohibited. A partnership of this kind was called a societas leonina. This article attempts to answer the question whether the Commentators contributed to the development of this institution.